Adaptation and altitude sickness: A 40-year bibliometric analysis and collaborative networks - Zila-Velasque, J. Pierre; Grados-Espinoza, Pamela; Morán-Mariños, Cristian; Morales Pocco, Kevin O.; Capcha-Jimenez, Uriel S.; Ortiz-Benique, Zhamanda N. (Frontiers in Public Health, 2023)
Introduction: We analyze the scientific production and collaboration networks of studies based on adaptation and altitude diseases in the period 1980–2020. Methods The publications were extracted from journals indexed in Scopus. The bibliometric analysis was used to analyze the scientific production, including the number of annual publications, the documents, and the characteristics of the publications. With the VOSviewer software, the analysis of collaborative networks, productivity of the countries, as well as the analysis of the co-occurrence of keywords were visualized. Results 15,240 documents were registered, of which 3,985 documents were analyzed. A significant trend was observed in the number of publications (R2: 0.9847; P: < 0.001), with annual growth of 4.6%. The largest number of publications were original articles (77.8%), these published more frequently in the journal “Altitude Medicine and Biology”. The largest number of countries were from Europe and Asia; however, the largest collaboration network was with the United States. Of the countries with high altitudes, China and Peru ranked first in scientific productivity. The research priorities were on the adaptation mechanism (37.1%), mainly anoxia and respiratory function. Acute mountain sickness (18.4%) and pulmonary edema (14.7%) were the most reported diseases. Of the top 10 institutions, “University of Colorado” and “Universidad Peruana Cayetano Heredia” contributed more than 100 publications. Conclusions Scientific production on adaptation and altitude illnesses continues to grow. The United States and United Kingdom present collaborative networks with high-altitude countries. The research is aimed at studying the mechanisms of adaptation to altitude and acute mountain sickness.